Association analysis between feed efficiency studies and expression of hypothalamic neuropeptide genes in laying ducks. (22nd June 2016) - Zeng, T.; Chen, L.; Du, X.; Lai, S. J.; Huang, S. P.; Liu, Y. L.; Lu, L. Z.
Summary: Residual feed intake (RFI) is now considered a more reasonable metric to evaluate animal feed efficiency. In this study, the correlation between RFI and other feed efficiency traits was investigated and gene expression within the hypothalamus was determined in low RFI (LRFI) and high RFI (HRFI) ducks. Further, several hypothalamic neuropeptide genes were measured using quantitative real‐time PCR. The mean feed intake value was 160 g/day, whereas the egg mass laid (EML) and body weight were approximately 62.4 g/day and 1.46 kg respectively. Estimates for heritability of RFI, feed conversion ratio (FCR) and feed intake were 0.26, 0.18 and 0.23 respectively. RFI is phenotypically positively correlated with feed intake and FCR ( P  <   0.01). The expression of neuropeptide Y ( NPY ) and neuropeptide Y receptor Y5 ( NPY5R ) mRNA was higher in HRFI ducks compared with LRFI ducks ( P  <   0.05), whereas that of proopiomelanocortin ( POMC ), melanocortin 4 receptor ( MC4R ) and cholecystokinin ( CCK ) was lower ( P  <   0.05). The mRNA expression of gonadotropin‐releasing hormone 1 (luteinizing‐releasing hormone) ( GNRH1 ) and prolactin receptor ( PRLR ) was unchanged between LRFI and HRFI ducks. The results indicate that selection for LRFI could reduce feed intake without significant changes in EML, whereas selection on FCR will increase EML.